Visualizing Uncertainties, or How Albert Hirschman and the World Bank Disagreed on Project Appraisal and Development Approaches - Alacevich, Michele (World Bank, Washington, DC, 2014)
Since its birth in 1944, the World Bank has had a strong focus on development projects. Yet, it did not have a project evaluation unit until the early 1970s. An early attempt to conceptualize project appraisal had been made in the 1960s by Albert Hirschman, whose undertaking raised high expectations at the Bank. Hirschman's conclusions -- published first in internal Bank reports and then, as a book in 1967 -- disappointed many at the Bank, primarily because they found it impractical. Hirschman wanted to offer the Bank a new vision by transforming the Bank's approach to project design, project management and project appraisal. What the Bank expected from Hirschman, HOWEVER, was not a revolution but an examination of the Bank's projects and advice on how to make project design and management more measurable, controllable, and suitable for replication. The history of this failed collaboration provides useful insights on the unstable equilibrium between operations and evaluation within the Bank. In addition, it shows that the Bank actively participated in the development economics debates of the 1960s. This should be of interest for development economists today who reflect on the future of their discipline emphasizing the need for a non-dogmatic approach to development. It should also be of interest for the Bank itself, which is stressing the importance of evaluation for effective development policies. The history of the practice of development economics, using archival material, can bring new perspectives and help better understand the evolution of this discipline.